The marine fauna of New Zealand Stylasteridae (Cnidaria hydroida). - Cairns, Stephen D. (Aukland, New Zealand NZ Oceanographic Institute, 1989)
New Zealand Oceanographic Institute Memoirs; 98
Keywords: Hydroida; Stylasteridae; Marine fauna